Impact of Pre-Diabetes on the Rate of Major Adverse Cardiovascular Events in Patients Undergoing Coronary Artery Bypass Grafting - A. N. Sumin; N. A. Bezdenezhnykh; A. V. Bezdenezhnykh; S. V. Ivanov; O. L. Barbarash (Рациональная фармакотерапия в кардиологии)
Aim. To assess  the  relationship between pre-diabetes/type 2 diabetes mellitus (type 2 DM) and  long-term adverse  prognosis in patients with coronary  artery disease (CAD) who underwent coronary  artery bypass grafting (CABG).Material and methods. 347 CAD patients who underwent CABG in the period from 2006 to 2009 were enrolled into the study. All patients were divided into 3 groups:  148 patients with type 2 DM (the median age – 58 years, the median follow-up – 1.8  years), 23 patients with pre-diabetes, i.e. impaired fasting glycemia and/or impaired glucose tolerance (the median age – 58 years, the median follow-up – 1.7  years); and 176 patients without diabetes and other carbohydrate metabolism disorders (CMD) (the median age – 58 years, the median follow-up – 1.7 years). The prognosis was considered as unfavorable in case of any major adverse  cardiovascular events  (MACEs) defined as myocardial infarction, stroke,  cardiovascular death. Logistic regression was used to identify the predictors of the unfavorable prognosis.Results. All patients in the study groups were comparable in age (p=0.345) and the median of the follow-up (p=0.134). The comparative assessment of the long-term prognosis showed the similar rate of major adverse  cardiovascular events in the groups  with CMD (the diabetes group  – 14.2% vs the  pre-diabetes group  – 13.0%), compared to 6.3% in patients without any CMD (p=0.028 for the  groups  with DM and  without CMD). The regression analysis reported that type 2 DM appeared to be a significant factor associated with the development of the long-term MACEs (odds ratio [OR] 3.307, 95% confidence interval [95%CI] 1.372-7.968, p=0.007). The addition of pre-diabetes as a potential predictor of the unfavorable prognosis increased 3.6-fold the risk of long-term MACEs (OR 3.617; 95%CI 1.557-8.403, p=0.001).Conclusion.  Pre-diabetes  significantly  affects  the  prognosis  of patients  after  CABG, similarly  to type  2 DM. The diagnosis  of CMD in  patients undergoing CABG is of significant clinical relevance.